2001
DOI: 10.1021/la0105533
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Surfactant Lamellar Phase and a Strictly Alternating Comb-Graft Amphiphilic Polymer Based on PEG

Abstract: We study the effect of hydrophobically modified polymers (hm-polymers) on the phase behavior and membrane elastic properties of the lyotropic lamellar (LR) phase of the nonionic surfactant penta(ethylene glycol) dodecyl ether (C12E5). The hm-polymer is a model comb-graft polymer with monodisperse PEG blocks (loops) of 6, 12, or 35 kg/mol connecting C18 stearylamide hydrophobes. The polymer is of interest because both its loops and hydrophobes are biocompatible. The membrane properties are extracted from the sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 31 publications
(71 reference statements)
2
29
0
Order By: Relevance
“…Influence of the grafted polymers on the elastic properties has been carefully investigated by some researchers. [25][26][27]30,34,41,42,[46][47][48][49] It is known that grafting polymers enhances the bending modulus and the repulsive interaction between membranes. Castro-Roman et al explained the enhancement of the repulsive Helfrich interaction by renormalizing the thickness of polymer layer into an effective thickness of membranes.…”
Section: Development Of the Oily Streak Networkmentioning
confidence: 99%
“…Influence of the grafted polymers on the elastic properties has been carefully investigated by some researchers. [25][26][27]30,34,41,42,[46][47][48][49] It is known that grafting polymers enhances the bending modulus and the repulsive interaction between membranes. Castro-Roman et al explained the enhancement of the repulsive Helfrich interaction by renormalizing the thickness of polymer layer into an effective thickness of membranes.…”
Section: Development Of the Oily Streak Networkmentioning
confidence: 99%
“…Storage modulus G′ versus oscillation frequency for the bare membrane system (φ ) 0.2) measured after shearing the system at the corresponding shear rate for 2 h. The shear strain is fixed at 3%, which is located in the linear region. The ratio of the product κB h of the hmPAA3%250kpoC 14doped membrane to that of the hmPAA1.5%250kpoC 14doped membrane systems can be calculated by (η 1.5% /η 3% ) 2 on the basis of the definition of the Caille `constant of η ) q o 2 k B T/8π κB h /d because the first-order Bragg peak position q o and the interlamellar spacing d are independent of hydrophobe substitution levels. On the basis of our previous SANS study, 1,2 κB h of the hmPAA3%-250kpoC 14 -doped membrane system is 1.8 times that of the hmPAA1.5%250kpoC 14 -doped membrane system.…”
Section: Figurementioning
confidence: 99%
“…5 Following a concept originally proposed by Whitesides, 6 Prud'homme and co-workers recently demonstrated that multivalent polymers provide a cooperative mechanism for stabilization of liposomes and other colloidal particles. [7][8][9][10][11] It was conjectured that, in comparison to polymers with single binding site per chain, polymers with multiple binding sites (i.e., multivalency) can lead to a stronger overall surface absorption thus a higher level of surface protection even when the binding energy for each site is relatively weak. In other words, long polymers with multiple binding sites are more efficient than short polymers with only a single binding site at the same composition.…”
Section: Introductionmentioning
confidence: 99%